Can a water market avert the "double-whammy" of trade reform and lead to a "win-win" outcome? - Diao, Xinshen; Roe, Terry L. (Elsevier, 2003)
This paper focuses on the linkages between water and trade policies, using Morocco as a case. This country is typical of many in that policy protects its import competing agricultural and industrial sectors while water in irrigated agriculture is priced below its marginal value product. Changing water policy without correcting for these other distortions leads to a more inefficient allocation of water. On the other hand, reforming trade policy alone can make farmers growing crops protected pre-reform worse off. Using an intertemporal, applied general equilibrium model, we find that trade reform actually creates an opportunity to pursue water policy reform. Creating a water user-rights market post trade reform not only compensates for the decline in farmers’ profits caused by the trade reform, but also raises the efficiency of water allocation and hence benefits the economy as a whole. -- Online Abstract